Phase equilibria in NaAlSiO4–KAlSiO4–SiO2–H2O at 100 MPa pressure: equilibrium leucite composition and the enigma of primary analcime in blairmorites revisited. (February 2014) - Henderson, C. M. B.; Hamilton, D. L.; Waters, J. P.
Abstract: Experiments in the system NaAlSiO4 (Ne)−KAlSiO4 (Ks)−SiO2 (Qz)−H2 O at 100 MPa show that the maximum content of NaAlSi2 O6 in leucite is ∼4 wt.% and that analcime is close to the stoichiometric composition (NaAlSi2 O6 .H2 O). Analcime forms metastably on quenching the higher-temperature experiments; it is secondary after leucite in experiments quenched from 780°C, while from 850°C it forms by alteration of leucite, and by devitrification of water-saturated glass. Both processes involve reaction with Na-rich aqueous fluids. Stable analcime forms at 500°C, well below the solidus, and cannot form as phenocrysts in shallow volcanic systems. New data for natural analcime macrocrysts in blairmorites are presented for the Crowsnest volcanics, Alberta, Canada. Other researchers have suggested that primary analcime occurs as yellow-brown, glassy, analcime phenocrysts. Our microprobe analyses show that such primary analcime is close to stoichiometric, with very low K2 O (<0.1 wt.%), minor Fe2 O3 (0.5−0.8 wt.%) and CaO (∼0.5 wt.%). An extrapolation of published experimental data for Ne−Ks−Qz at >500 MPa PH2 O, where Anl + melt coexist, suggests that at >800 MPa two invariant points are present: (1) a reaction point involving Kf + Ab + Anl + melt + vapour; and (2) a eutectic with Kf + Anl + Ne + melt + vapour. We suggest that the nepheline-free equilibrium mineral assemblage for Crowsnest samples is controlled by reaction point (1). In contrast, blairmorites from Lupata Gorge, Mozambique, form at eutectic (2), consistent with the presence of nepheline phenocrysts. Our conclusions, based on high- vs . low-pressure experiments, confirm the suggestion made by other authors, that Crowsnest volcanic rocks must have been erupted explosively to preserve glassy analcime phenocrysts during very rapid, upward transport from deep in the crust (H2 O pressures ≫500 MPa). Only rare examples survived the deuteric and hydrothermal alteration that occurred during and after eruption.